Polymorphonuclear Leukocyte-Platelet Interaction: Role of P-Selectin in Thromboxane B2 and Leukotriene C4 Cooperative Synthesis - Maugeri, Norma; Evangelista, Virgilio; Celardo, Antonio; Dell’Elba, Giuseppe; Martelli, Nicola; Piccardoni, Paola; de Gaetano, Glovanni; Cerletti, Chiara (Thrombosis and Haemostasis, 1994)
In PMN/platelet suspensions stimulated by fMLP giant mixed aggregates are formed and TxB2 and LTC4 are synthesized as the result of the cooperation in the arachidonic acid (AA) metabolism during cell/cell contact. PMN-derived cathepsin G induced the expression of P-selectin on platelet surface. GE12, an antibody against P-selectin, significantly reduced mixed cell aggregates. GE12 did not affect platelet aggregation induced by PMN-derived supernatants, indicating that the inhibitory effect of GE12 on mixed cell aggregation depends on inhibition of PMN/platelet adhesion. GE12 significantly reduced TxB2 and LTC4 production in PMN/platelet mixed cell suspensions stimulated by fMLP. As previously reported, synthesis of 3H-TxB2 in 3H-AA-labeled PMN/unlabeled platelets indicates that platelets utilize 3H-AA from PMN. 3H-LTC4 production in unlabeled PMN/3H-AA-labeled platelets indicates that bidirectional routes are utilized in this system for LTC4 synthesis. GE12 significantly reduced 3H-TxB2 and 3H-LTC4 synthesis. These results show that cathepsin G released by activated PMN induces the expression of P-selectin on platelet membrane: this adhesive glycoprotein modulates cell-cell contact and transcellular metabolism of AA.